(untitled) (The Research of Medical Science Review, 2025)
Introduction: Infection control is a cornerstone of safe healthcare delivery, particularly in preventing healthcare-associated infections (HAIs). Standard precautions, including proper use of personal protective equipment (PPE) and safe handling of contaminated materials, are critical for nursing professionals. However, gaps in knowledge and practice among nursing students can compromise patient safety. This study evaluates the knowledge and practice of standard precautions for infection control among Generic Bachelor of Science in Nursing (BSN) students in public sector institutions in Lahore, Pakistan, to identify areas for educational improvement. Method: A cross-sectional descriptive survey was conducted over three months, involving 170 BSN 1st and 2nd-year students from the College of Nursing at Services Hospital Lahore and Allama Iqbal Medical College, Lahore. A convenience sampling technique was used to recruit participants. Data were collected using an adapted Knowledge, Attitude, and Practice (KAP) questionnaire, consisting of demographic data, 18 knowledge-based questions (Yes/No/Don’t Know), and 16 practice-based questions (Never/Sometimes/Always). The questionnaire was distributed in printed form, with 30 minutes provided for completion. Data were analyzed using SPSS version 21, employing descriptive statistics (frequencies, percentages, tables, and graphs) and independent t-tests to compare knowledge and practice. Ethical considerations included obtaining informed consent and ensuring participant confidentiality. Results: The sample comprised 85.9% female students, 46.5% aged 22-24 years, 54.7% married, and a near-even distribution of 1st-year (48.8%) and 2nd-year (51.2%) students. Knowledge assessment revealed significant gaps: only 33.5% correctly identified the need to discard needles in sharp boxes, 34.7% recognized the necessity of surgical gloves in all patient care procedures, and 32.4% understood that standard precautions apply universally. Practice-related responses showed inconsistencies, with 39.4% unsure about precautions for contact with patient sweat and 44.1% incorrectly believing precautions were unnecessary for urine or stool contact. High levels of uncertainty (e.g., 36.5% for isolation gown use) underscored challenges in translating knowledge into practice. ConclusionsThe study highlights notable deficiencies in BSN students’ knowledge and practice of standard precautions, indicating a need for enhanced educational interventions. Targeted training, hands-on simulations, and curriculum enhancements are essential to address misconceptions, improve competency, and ensure consistent application of infection control protocols. Strengthening these areas will better prepare nursing students to prevent HAIs and enhance patient safety.